Breach of Mortgagee's Duties of Sale - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2009)
Comments on the Singapore Court of Appeal decision in Beckkett v Deutsche Bank on the duties owed by a mortgagee in exercising its power of sale of the mortgaged property comprising shareholdings in various unlisted companies and whether a shareholder-mortgagor can claim for losses arising from the sale of its shareholding in a company at an undervalue where the reason for the undervalue is the breach of duty by the mortgagee to the company